Estudio del efecto de quemas recientes sobre el microclima del suelo en el páramo de la Reserva ecológica El Ángel, en el maco del proyecto: Estudio de Paja (Calamagrostis sp) y Achupalla (Puya hamata) como especies indicadoras de la historia de fuegos recientes en el páramo de la Reserva ecológica Los Ilinizas y la Reserva ecológica El Ángel - Marchán Moncayo, Mario Alejandro (2016)
The Andean highlands have become an important focus of conservation and harboring high biodiversity and provide various environmental services. The riots in this ecosystem have grown over time, either by agriculture, deforestation, mining and other activities. One threat that has affected a large expanse of moorland fires are manmade. In the present study the effect of fires on the soil microclimate in the Ecological Reserve El Angel, Carchi, Ecuador for which variables as the amount of light reaching under vegetation and soil temperature was evaluated was analyzed. It was determined that there is a negative correlation between the percentage of light that reaches the ground and the time after burning, burned areas a year ago have 2ºC (approximately) rather than burned areas 10 years ago, resulting in a relationship directly between the variables of quantity of light reaching under vegetation and soil temperature affecting explicitly soil microclimate.